2020
DOI: 10.1101/2020.03.03.975540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Globus pallidus dynamics reveal covert strategies for behavioral inhibition

Abstract: Flexible behavior requires restraint or cancellation of actions that are no longer appropriate. This behavioral inhibition critically relies on frontal cortex -basal ganglia circuits. A central node within the basal ganglia, the globus pallidus pars externa (GPe), has been hypothesized to mediate "proactive" inhibition: being prepared to stop an action if needed. Here we investigate the population dynamics of rat GPe neurons during preparation-to-stop, stopping, and going.Rats could selectively engage proactiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 69 publications
1
10
1
Order By: Relevance
“…SNr is a basal ganglia output nucleus, receiving converging inputs from multiple basal ganglia structures including GPe. The finding that SNr decodes behavioral output more selectively and accurately compared to GPe is consistent with the idea that SNr is closer to post-decision behavioral outputs, whereas GPe represent internal preparatory states [72].…”
Section: Decoding Behavioral Condition From Neural Activity With a Smsupporting
confidence: 84%
See 2 more Smart Citations
“…SNr is a basal ganglia output nucleus, receiving converging inputs from multiple basal ganglia structures including GPe. The finding that SNr decodes behavioral output more selectively and accurately compared to GPe is consistent with the idea that SNr is closer to post-decision behavioral outputs, whereas GPe represent internal preparatory states [72].…”
Section: Decoding Behavioral Condition From Neural Activity With a Smsupporting
confidence: 84%
“…We used the spike count in the first 100 ms after the rat exited the center port to predict the behavioral condition (left or right). Further details on the surgical, experimental, and preprocessing steps can be found in [72].…”
Section: Recordings From Basal Gangliamentioning
confidence: 99%
See 1 more Smart Citation
“…Lesioning or inactivation studies were largely inconclusive, as these manipulations did not result in a consistent motor phenotype (Norton, 1976;Ossowska et al, 1983;Schneider and Olazabal, 1984;Hauber et al, 1998;Joel et al, 1998;Konitsiotis et al, 1998;Soares et al, 2004;Hegeman et al, 2016). A large number of studies showed that GPe neurons change their activity in relation to movement; however, the identity of the recorded neurons was unknown (DeLong, 1971;Anderson, 1978;Anderson and Horak, 1985;DeLong et al, 1985;Mink and Thach, 1987;Mitchell et al, 1987;Filion et al, 1988;Nambu et al, 1990;Mink and Thach, 1991b, a;Mushiake and Strick, 1995;Parent and Hazrati, 1995;Kimura et al, 1996;Arkadir et al, 2004;Shin and Sommer, 2010;Schmidt et al, 2013;Yoshida and Tanaka, 2016;Gu et al, 2020;Mullie et al, 2020). It has been shown that identified GPe neuron subtypes can display diverse changes in their activity during spontaneous body movements (Dodson et al, 2015).…”
Section: Gpe Neuron Subtypes Have Opposing Roles In Motor Controlmentioning
confidence: 99%
“…Although the importance of the GPe has long been recognized, our understanding of its cell types, their organization, and their functional properties is limited. While prior studies argue GPe neurons are involved in movement control (Dodson et al, 2015; Zimnik et al, 2015; Glajch et al, 2016; Mastro et al, 2017; Aristieta et al, 2020; Gu et al, 2020; Pamukcu et al, 2020), precisely how they are involved in motor function and dysfunction remains poorly defined. A major hurdle has been imposed by the complexity of the cellular makeup of the GPe.…”
Section: Introductionmentioning
confidence: 99%